2022
DOI: 10.1177/00220345221108699
|View full text |Cite
|
Sign up to set email alerts
|

Public Valuation of Direct Restorations: A Discrete Choice Experiment

Abstract: Direct posterior dental restorations are commonly provided following management of dental caries. Amalgam use has been phased down and the feasibility of a phase-out by 2030 is being explored. Alternative direct restorative materials differ in their outcomes and provision. This research aimed to elicit the UK population’s preferences for different attributes of restorations and their willingness to pay (WTP) for restorative services and outcomes. A discrete choice experiment (DCE) was designed with patient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies [ 25 , 26 , 27 , 28 , 29 ] have found that women prefer composite restorations, whereas men prefer amalgam restorations. They have also noted a preference for composite restorations, which are generally more expensive in areas with higher socioeconomic status, while amalgam (which is generally less expensive) is preferred amongst those of a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 25 , 26 , 27 , 28 , 29 ] have found that women prefer composite restorations, whereas men prefer amalgam restorations. They have also noted a preference for composite restorations, which are generally more expensive in areas with higher socioeconomic status, while amalgam (which is generally less expensive) is preferred amongst those of a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%